Effect of hydroalcoholic Plectranthus vettiveroides in glycerol-induced acute renal failure in rats (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The goal of this study was to see if hydroalcoholic extract of leaves of Plectranthus vettiveroides(HEPV) might help rats with glycerol-induced acute renal failure (ARF). The rats were given a single intramuscular injection of hypertonic glycerol (50 percent v/v; 8 ml/kg) to induce rhabdomyolytic ARF, and the animals were euthanized after 24 hours. The degree of renal damage was determined using plasma creatinine, blood urea nitrogen, creatinine clearance, and histological investigations. In a dose-dependent manner, pre-treatment with HEPV (125 and 250 mg/kg p.o. twice daily for 3 days) substantially reduced hypertonic glycerol-induced renal impairment. To investigate the mechanism of HEPV's renoprotective effects, researchers used BADGE (Bisphenol-A-diglycidyl ether) (30 mg/kg), a PPAR antagonist, and N(omega)-nitro-l-arginine-methyl ester (L-NAME) (10, 20, and 40 mg/kg), a nitric oxide synthase inhibitor. The therapeutic effects of HEPV in glycerol-induced renal impairment were reversed when BADGE (30 mg/kg) and L-NAME (40 mg/kg) were given. The hydroalcoholic extract of Plectranthus vettiveroides leaves has the ability to reduce myoglobinuric renal failure, and its renoprotective actions are mediated via activation of the PPAR and nitric oxide-dependent signalling pathways.